The Effect of Labor Epidural Analgesia on Breastfeeding Outcomes: A Prospective Observational Cohort Study in a Mixed-Parity Cohort. (September 2019) - Orbach-Zinger, Sharon; Landau, Ruth; Davis, Atara; Oved, Oren; Caspi, Liron; Fireman, Shlomo; Fein, Shai; Ioscovich, Alexander; Bracco, Danielle; Hoshen, Moshe; Eidelman, Leonid A.
Abstract : BACKGROUND: The effect of labor epidural analgesia (LEA) on successful breastfeeding has been evaluated in several studies with divergent results. We hypothesized that LEA would not influence breastfeeding status 6 weeks postpartum in women who intended to breastfeed in an environment that encourages breastfeeding. METHODS: In this prospective observational cohort study, a total of 1204 women intending to breastfeed, delivering vaginally with or without LEA, were included; breastfeeding was recorded at 3 days and 6 weeks postpartum. Primary outcome was breastfeeding at 6 weeks, and the χ 2 test was used for comparisons between women delivering with and without LEA, according to parity status and previous breastfeeding experience. Total epidural fentanyl dose and oxytocin use (yes/no) were recorded. A multivariable logistic regression was performed to assess factors affecting breastfeeding at 6 weeks. RESULTS: The overall breastfeeding rate at 6 weeks was 76.9%; it was significantly lower among women delivering with LEA (74.0%) compared with women delivering without LEA (83.4%; P < .001). Among 398 nulliparous women, 84.9% delivered with LEA, compared with 61.8% of multiparous women ( P < .001). Multiparous women (N = 806) were more likely to breastfeed at 6 weeks (80.0% vs 70.6% nullipara; P < .001). Using multivariable logistic regression that accounted for 14 covariates including parity, and an interaction term between parity and LEA use, LEA was significantly associated with reduced breastfeeding at 6 weeks (odds ratio, 0.60; 95% confidence interval, 0.40–0.90; P = .015). In a modified multivariable logistic regression where parity was replaced with previous breastfeeding experience, both as a covariate and in the interaction term, only previous breastfeeding experience was associated with increased breastfeeding at 6 weeks (odds ratio, 3.17; 95% confidence interval, 1.72–5.80; P < .001). CONCLUSIONS: In our mixed-parity cohort, delivering with LEA was associated with reduced likelihood of breastfeeding at 6 weeks. However, integrating women's previous breastfeeding experience, the breastfeeding rate was not different between women delivering with and without LEA among the subset of multiparous women with previous breastfeeding experience. Therefore, our findings suggest that offering lactation support to the subset of women with no previous breastfeeding experience may be a simple approach to improve breastfeeding success. This concept subscribes to the notion that women at risk for an undesired outcome be offered tailored interventions with a personalized approach.